2021
DOI: 10.3390/ani11092534
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Fusarium Mycotoxins on the Liver of Gilts and Their Suckling Piglets

Abstract: Mycotoxins are common fungal secondary metabolites in both animal feed and human food, representing widespread toxic contaminants that cause various adverse effects. Co-contamination with different mycotoxins is frequent; therefore, this study focused on feed contaminated with Fusarium mycotoxins, namely, deoxynivalenol (5.08 mg/kg), zearalenone (0.09 mg/kg), and fusaric acid (21.6 mg/kg). Their effects on the liver of gilts and their piglets were chosen as the research subject as pigs are one of the most sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
(90 reference statements)
1
3
0
Order By: Relevance
“…In fact, significant fibrosis with the evidence of hepatocyte degradation can be observed in the ZEN+ group's livers. These findings are consistent with previous studies from the literature in which liver lesions and alterations of some enzymatic indices of the hepatic function were detected in rats [41], rabbits [42], and gilts [43], as well as Polish wild boars [44], after ZEN exposure. Moreover, hepatocyte degeneration found in the livers supports the notion that ZEN is a potent apoptosis inductor in the mammalian system in a dose-and time-dependent manner, as previously reported by in vivo and in vitro experiments [45,46].…”
Section: Discussionsupporting
confidence: 93%
“…In fact, significant fibrosis with the evidence of hepatocyte degradation can be observed in the ZEN+ group's livers. These findings are consistent with previous studies from the literature in which liver lesions and alterations of some enzymatic indices of the hepatic function were detected in rats [41], rabbits [42], and gilts [43], as well as Polish wild boars [44], after ZEN exposure. Moreover, hepatocyte degeneration found in the livers supports the notion that ZEN is a potent apoptosis inductor in the mammalian system in a dose-and time-dependent manner, as previously reported by in vivo and in vitro experiments [45,46].…”
Section: Discussionsupporting
confidence: 93%
“…Further studies of the gene expression profiles of pig liver showed that DON and ZEN induced significant changes in the overall transcriptome ( 13 ). Furthermore, sows fed with diets containing DON, ZEN, and fusaric acid significantly increased hepatocyte necrosis, apoptosis, and sinusoidal leukocytes with mixed inflammatory infiltration in hepatic lobules, with apoptotic hepatocytes increasing significantly in the hepatic sinuses of experimental sows ( 14 ).…”
Section: Systemic Toxicity Of Mycotoxinsmentioning
confidence: 98%
“…Besides intestinal tract, liver is the other major organ of ZEA metabolism in mammals (Malekinejad et al., 2006). Research has found that the apoptosis rates of hepatocytes and mixed inflammatory infiltration of liver lobule were significantly increased in gilts fed an experimental diet contaminated with ZEA (0.09 mg/kg) (Dolensek et al., 2021). Notably, ZEA can significantly increase the serum levels of AST, ALT, ALP, LDH, and other antioxidant enzymes such as SOD, CAT, and GSH in mice (AbuZahra et al., 2021).…”
Section: Effects Of Zea‐mediated Toxicity In Mammalsmentioning
confidence: 99%